The Role of pH in PEG-b-PAAc Modification of Gadolinium Oxide Nanostructures for Biomedical Applications - Eva Hemmer; Nallusamy Venkatachalam; Hiroshi Hyodo; Kohei Soga (Advances in Materials Science and Engineering)
Upconversion and near-infrared emitting Gd2O3:Er3+,Yb3+ nanostructured phosphors (nanoparticles and nanorods) for applications in bioimaging have been synthesized by precipitation methods and hydrothermal treatment. Variation of the material synthesis conditions (additives and pH) allows controlling particle size (40 nm to μm range) and rod aspect ratio (5 to 18). It was shown that PEG-b-PAAc (poly(ethylene glycol) poly(acrylic acid) block polymer) is suitable to provide the required chemical durability, dispersion stability, and noncytotoxic behaviour for biomedical applications, where the coating of Gd2O3 with a protecting and biocompatible layer is essential in order to prevent the release of toxic Gd3+ ions. Physicochemical properties of the Gd2O3:Er3+,Yb3+ nanostructures modified with PEG-b-PAAc have been investigated by TG-DTA, FT-IR, and DLS revealing a strong influence of modification conditions, namely, pH of the reaction media, on the nature of the PEG-b-PAAc layer.